PEMBENTUKAN ASEAN SECURITY COMMUNITY (ASC) DI KAWASAN ASIA TENGGARA - Dewa Gede Sudika Mangku (Faculty of Law, Mahasaraswati University, Denpasar, 2019)
The ASEAN Community consists of 3 (three) pillars, namely the ASEAN Security Community (ASC), the ASEAN Economic Community (AEC) and the ASEAN SocioCultural Community (ASCC) that are mutually binding and strengthen to achieve common goals in order to ensure sustainable peace, stability and prosperity that is divided in the Southeast Asia region. These three pillars supporting the ASEAN Community are a new paradigm that will drive ASEAN cooperation towards a community and a new, more binding identity. ASC must be a mechanism to solve problems internally which has the potential to disrupt the stability and security of the region through peaceful means. Including sensitive issues that have the potential to cause problems without having to abandon the principle of not interfering in the affairs of other countries.